Comparing the Effectiveness of Information Framing Strategy on Utilitarian and Hedonic Food Product Packaging - Sony Kusumasondjaja (Jurnal Manajemen & Agribisnis, 2018)
The increasing adoption of framing strategy among food marketers and advertisers generates inquiries about the effectiveness of the strategy. Product messages with different framing strategy are expected to stimulate different consumer responses. This research investigates the difference of consumer attitude and purchase intention towards the framed product when consumers are exposed to food labels with different types of food product (hedonic vs utilitarian) using different framing strategy (positive vs negative). A lab experimental design was prepared involving 160 participants. Chocolate was examined to represent hedonic product while packaged milk was used as utilitarian product. Data were analyzed using ANOVA and multiple linear regression. Findings suggested that the effectiveness of framing strategy was moderated by product type. Positive framing was found to be more effective for hedonic food products, while for utilitarian food product, it was more favorable to adopt negative framing.